Effect of intracranial pressure on photoplethysmographic waveform in different cerebral perfusion territories: A computational study - Liu, Haipeng; Pan, Fan; Lei, Xinyue; Hui, Jiyuan; Gong, Ru; Feng, Junfeng; Zheng, Dingchang (Frontiers in Physiology, 2023)
Background: Intracranial photoplethysmography (PPG) signals can be measured from extracranial sites using wearable sensors and may enable long-term non-invasive monitoring of intracranial pressure (ICP). However, it is still unknown if ICP changes can lead to waveform changes in intracranial PPG signals. Aim: To investigate the effect of ICP changes on the waveform of intracranial PPG signals of different cerebral perfusion territories. Methods: Based on lump-parameter Windkessel models, we developed a computational model consisting three interactive parts: cardiocerebral artery network, ICP model, and PPG model. We simulated ICP and PPG signals of three perfusion territories (anterior, middle, and posterior cerebral arteries, all right side) in three ages (20, 40, and 60 years) and four intracranial capacitance conditions (normal, 20% decrease, 50% decrease, and 75% decrease). We calculated following PPG waveform features: maximum, minimum, mean, amplitude, min-to-max time, pulsatility index (PI), resistive index (RI), and max-to-mean ratio (MMR). Results: The mean ICPs in normal condition were in the normal range (8.87-11.35 mmHg), with larger PPG fluctuations in older subject and ACA/PCA territories. When intracranial capacitance decreased, the mean ICP increased above normal threshold (>20 mmHg), with significant decreases in maximum, minimum, and mean, a minor decrease in amplitude, and no consistent change in min-to-max time, PI, RI, or MMR (maximal relative difference was less than 2%) for PPG signals of all perfusion territories. There are significant effects of age and territory on all waveform features except age on mean. Conclusion: ICP values could significantly change the value-relevant (maximum, minimum, and amplitude) waveform features of PPG signals measured from different cerebral perfusion territories, with negligible effect on shape-relevant features (min-to-max time, PI, RI, and MMR). Age and measurement site could also significantly influence intracranial PPG waveform.